THE FITTING OF SARIMA MODEL ON PEADS PATIENTS COMING AT OUTPATIENTS MEDICAL LABORATORY (OPML), MAYO HOSPITAL, LAHORE - Muhammad Ibrahim; Muhammad Jamil; Safoora Akbar et al. (Journal of University Medical & Dental College, 2016)
ABSTRACTBACKGROUND & OBJECTIVE: Forecasting medical phenomena like the patients volume, emergency overcrowding, stay length in hospital on surgical procedure and bed occupancy in hospital wards, patients' inﬂux or patient arrival drawn considerable attention since last two decades. This study was carried out to ﬁt a best uni-variate ARIMA model (Box-Jenkin Methodology) to forecast the Pediatrics patient's incoming at Outpatients Medical Laboratory (OPML), Outpatients Department (OPD), Mayo Hospital, Lahore to determine any seasonal impact on patient's incoming. METHOD: Time series data of Peads patients coming/reporting in OPML, OPD Mayo Hospital Lahore, from September 2007 to December 2013 were used for ﬁtting the best model. RESULT & CONCLUSION: The appropriate model for Peads data as ARIMA (1, 1, 1) and SARIMA (1, 0, 1) at seasonal points=4 after residuals diagnostic checks. The estimated number of Peads patients in the month of January 2014 was 119 using ARIMA model and 92 using SARIMA model as compared to actual which is 102 patients. SARIMA model has ability to forecast the number of incoming patients accurately. It is now concluded that the ﬁtted SARIMA model showed a seasonal impact on incoming patients and can be used to forecast the patients' incoming to OPML, OPD for future planning and management to ensure quality diagnostic healthcare service to the patients/clinician.